Autobiography, poems and prayers - Parker, Theodore ([Parker, Theodore. Works. Centenary ed, 1911)
Autobiography: An autobiographical fragment ; The true idea of a Christian Church ; Some account of my ministry ; Of the position and duty of a minister -- Prayers -- Parables -- Experience as a minister -- Poems.